Life with the Pneumococcus : Notes from the Bedside, Laboratory, and Library - Austrian, Robert (University of Pennsylvania Press, 2016)
Because of the high fatality rate of untreated pneumococcal pneumonia, both the disease and its principal cause, the pneumococcus, were objects of intense scrutiny by physicians and bacteriologists during the last two decades of the nineteenth century and the first half of the twentieth. As a result, scientists learned much of the fundamental importance to microbiology, immunology, and genetics while developing the pneumococcal vaccine.